What is the value of entrepreneurship? A review of recent research - C. Mirjam van Praag; Peter H. Versloot (Institute for the Study of Labor (IZA), 2007)
This paper examines to what extent recent empirical evidence can collectively and systematically substantiate the claim that entrepreneurship has important economic value. Hence, a systematic review is provided that answers the question: What is the contribution of entrepreneurs to the economy in comparison to non-entrepreneurs? We study the relative contribution of entrepreneurs to the economy based on four measures that have most widely been studied empirically. Hence, we answer the question: What is the contribution of entrepreneurs to (i) employment generation and dynamics, (ii) innovation, and (iii) productivity and growth, relative to the contributions of the entrepreneurs' counterparts, i.e. the 'control group'? A fourth type of contribution studied is the role of entrepreneurship in increasing individuals' utility levels. Based on 57 recent studies of high quality that contain 87 relevant separate analyses, we conclude that entrepreneurs have a very important but specific function in the economy. They engender relatively much employment creation, productivity growth and produce and commercialize high quality innovations. They are more satisfied than employees. More importantly, recent studies show that entrepreneurial firms produce important spillovers that affect regional employment growth rates of all companies in the region in the long run. However, the counterparts cannot be missed either as they account for a relatively high value of GDP, a less volatile and more secure labor market, higher paid jobs and a greater number of innovations and they have a more active role in the adoption of innovations.
Keywords: 330; Entrepreneur; entrepreneurship; self-employment; productivity; economic development; growth; employment; innovation; patents; R&D; utility; remuneration; income; Unternehmer; Selbstständige; Produktivität; Wirtschaftswachstum; Beschäftigungseffekt; Innovation